FEATURES OF REBUILDING THE LIVING ENVIRONMENT IN AREAS DESTROYED BY MILITARY ACTION - Tykhonenko, Yuliia; Avdieieva, Nataliia; Avdieieva, Maryna (Theory and practice of design, 2025)
Purpose. The aim of the study is to identify and summarise the characteristics of the reconstruction of the living environment in areas destroyed by military action, taking into account modern requirements for safety, functionality, inclusiveness and environmental sustainability, as well as to analyse current Ukrainian and international experience in this field in order to find effective approaches to creating a new living environment. Methodology. The methodological basis of the study is based on a comprehensive interdisciplinary approach that combines analysis of existing Ukrainian and international experience with the reconstruction of the living environment in a post-war context. The work is based on a comparative analysis of spatial solutions, a study of the typology of damaged and new residential buildings, an urban planning assessment of the state of destroyed territories, as well as an analysis of current regulations governing the design, reconstruction and placement of residential and public buildings. Elements of graphic modelling and conceptual forecasts of the environment are applied, taking into account current challenges in the areas of security, inclusiveness, environmental sustainability and social adaptation of the population. The generalisation of the results of previous studies and practical experience [2], [3] provides material for identifying an approach at the present stage. The article is a continuation of the authors’ previous studies on the reconstruction of the residential environment [1], [4], etc. Results. The most important features affecting the reconstruction of the living environment in destroyed areas have been identified, in particular the need to integrate protective elements into the structure of residential buildings, re-evaluate outdated building types and introduce new functional and design solutions that emphasise flexibility, accessibility and comfort of living. It was found that it is advisable to combine traditional and innovative approaches in design, taking into account the social context and the real needs of the population. The importance of the quality of the visual and functional environment, green areas, recreational areas, protective infrastructure and public spaces as components of a new model of the living environment was confirmed. The study also made it possible to develop an approach to transforming damaged areas into more sustainable and safer ones. Scientific novelty. The scientific novelty lies in the fact that the peculiarities of developing an approach to rebuilding the living environment in areas destroyed as a result of hostilities have been identified and characterised, taking into account current trends in architecture and urban planning. The work proposes new approaches to the integration of sustainable and adaptive architectural solutions that not only provide a comfortable living environment for residents but also meet current environmental and energy efficiency requirements, taking into account psychological and social aspects. The contribution to modern science lies in expanding scientific knowledge on the restoration of the living environment in post-conflict situations. The proposed approaches contribute to the formation of new standards of architectural design in war-torn regions and can be used in international practice for the reconstruction of territories affected by military operations or natural disasters. Practical relevance. The practical significance of the work lies in the possibility of using the developed proposals for real projects to reconstruct the living environment in war-torn regions of Ukraine. The proposed solutions can serve as a basis for restoring the housing stock, taking into account the needs of local communities and integrating new technologies into the design of residential buildings.